2021
DOI: 10.1002/bdd.2295
|View full text |Cite
|
Sign up to set email alerts
|

Profiling pharmacokinetics of double‐negative T cells and cytokines via a single intravenous administration in NSG mice

Abstract: This study was intended to delineate the profile of double-negative T cells (DNTs) in NOD.Cg-Prkdc scid Il2rg tm1wj /SzJ mice and cytokines released from DNTs in vivo and in vitro. Total 4 � 10 7 cells of RC1012 injection per mice were intravenously infused.IFN-γ, TNF-α, IL-1β, IL-2, IL-4, IL-6, IL-10 were measured in vivo and in vitro. A quantitative polymerase chain reaction (PCR) was employed to determine the gene copies of Notch2-NLA per DNT cell from collected organs. Cytokines were significantly increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Phosphorylated STAT molecules translocate into the nucleus to upregulate inflammatory factors and cytotoxic ligands. 50 Given that DNTs secrete a wide range of inflammatory cytokines, 14 , 51 the significance of JAK-STAT signaling in DNT-AML interactions is currently being explored.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylated STAT molecules translocate into the nucleus to upregulate inflammatory factors and cytotoxic ligands. 50 Given that DNTs secrete a wide range of inflammatory cytokines, 14 , 51 the significance of JAK-STAT signaling in DNT-AML interactions is currently being explored.…”
Section: Discussionmentioning
confidence: 99%
“…While the above study monitored the total DNT levels in the treated patients, the level and persistence of donor-derived DNTs were not examined. Recent studies reported that ex vivo expanded human DNTs can persist for around 14-21 days in naïve mice [17,26]. However, DNT persistence in leukemiabearing hosts, which provides more clinically relevant settings, was never studied.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies highlight the importance of infused cell persistence for a favourable clinical outcome of ACT [19][20][21][22][23][24][25]. Previously, we and others have demonstrated that adoptively transferred human DNTs could persist in naïve NSG mice for 2-3 weeks [17,26]. However, DNT engraftment in a leukemia-bearing host may differ from those seen in naïve mice, as AML can hamper immune cell survival and anti-leukemic activity via immunosuppressive function or promote their function and persistence by providing stimulatory signals for T cells to proliferate [27].…”
Section: Dnt Persistence and Anti-leukemic Activity In Leukemia-bearing Hostsmentioning
confidence: 99%
See 1 more Smart Citation